2016
DOI: 10.1097/mib.0000000000000696
|View full text |Cite
|
Sign up to set email alerts
|

Host Immune Response to Clostridium difficile Infection in Inflammatory Bowel Disease Patients

Abstract: Background Clostridium difficile infection affects IBD patients. This study’s aim was to compare humoral response to C. difficile toxins in IBD and control outpatients. Methods We prospectively followed adult IBD and control subjects with serum and stool tested by PCR obtained at enrollment and during periods of CDI. Semi-quantitative serum levels of IgM, IgG and IgA to C. difficile toxins A and B were measured. Results 119 stool and 117 serum samples were obtained from 150 subjects. Different levels of Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
(58 reference statements)
0
6
1
Order By: Relevance
“…Both the incidence and severity of C. difficile infection have increased dramatically in the general population during the past two decades, and there has been an even higher increase among patients with IBD . The humoral immune response to the C. difficile toxins A and B is known to be protective in humans, but previous reports on seroreactivity to C. difficile in IBD patients have provided conflicting results . In summary, we found IgA levels in IBD to be no different from healthy controls but IgG to toxin A to be elevated similarly in both CD and UC and IgG to toxin B to be elevated only in CD.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Both the incidence and severity of C. difficile infection have increased dramatically in the general population during the past two decades, and there has been an even higher increase among patients with IBD . The humoral immune response to the C. difficile toxins A and B is known to be protective in humans, but previous reports on seroreactivity to C. difficile in IBD patients have provided conflicting results . In summary, we found IgA levels in IBD to be no different from healthy controls but IgG to toxin A to be elevated similarly in both CD and UC and IgG to toxin B to be elevated only in CD.…”
Section: Discussioncontrasting
confidence: 44%
“…Findings differing from ours may be attributed to inclusion of subjects with ongoing or recent C. difficile infection. Hughes et al . observed elevated IgA to both toxins in patients with infection and no IgG abnormalities in IBD; a strength of this study is more detailed clinical information than in our material, including ruling out a significant difference in antibiotic use during the prior 6 months between IBD patients and healthy controls.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…27, 28 The occurrence and severity of C. difficile infections in patients with IBD may in part relate to host factors such as immune response and changes in the gut microbiota. 29, 30 A recent case-control study found that the use of a TNF antagonist (not controlling for concomitant medications that included azathioprine or 6-mercaptopurine) was associated with an increased risk of opportunistic infection (odds ratio 4.4; 95% CI 1.1–17.0; P = 0.03), which may be due to systemic immunosuppression by TNF antagonists. 31 In addition, the risk of an opportunistic infection was found to be increased by the use of steroids in combination with other immunosuppressive agents.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the AhR-mediated pathway that protects mice from CDI, other pathways have been recognized as well for protection of mice from CDI, including innate and adaptive immune responses ( Hughes et al., 2016 ; Solomon, 2013 ). Our results showed that indole is a survival factor for C. diff and production of bacterial indole is inhibited by lactic acid induced by LELN-LS treatment.…”
Section: Discussionmentioning
confidence: 99%